2002
DOI: 10.1097/00004694-200201000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fifty patients up to 15 years of age with simple bone cysts were treated at the Department of Pediatric Surgery at the Children's Hospital Zagreb. There were 35 boys and 15 girls with 26 humeral cysts, 15 femoral cysts, 8 tibial cysts, and 1 radial cyst. There was one case of multilocularity of a simple bone cyst (in the humerus and femur). Among those cysts, 19 were multicameral (in the femur and humerus). The size of cysts was determined with regard to the length of the affected bone. Cysts involving up to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…18 Decompression can be done with multiple drill holes, 12 cannulated screws, 19 and different types of nails. 20 Many mixed methods approach the cyst on multiple levels such as percutaneous removal of cyst lining, curettage to break up septations, intramedullary decompression, and injection of calcium sulfate pellets. 16 To date, few comparative studies have been conducted (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…18 Decompression can be done with multiple drill holes, 12 cannulated screws, 19 and different types of nails. 20 Many mixed methods approach the cyst on multiple levels such as percutaneous removal of cyst lining, curettage to break up septations, intramedullary decompression, and injection of calcium sulfate pellets. 16 To date, few comparative studies have been conducted (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was suggested that cyst fluid would play an important role in its pathogenesis. The interleukin 1, the prostaglandins and proteolytic enzymes present in the cyst would start a great resorptive activity in the affected bone [1,26]. According to these findings, the continuous drainage of the cyst fluid and the continuous decompression of the cyst seem to be a reasonable option for the treatment of these lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Arguments in favour of non-surgical treatment of juvenile bone cysts include very low complication rates and very few recurrences as confirmed by our meta-analysis, whereby 95% CI from 0 to 84% should be considered critically. In this regard, recurrence rates of 18–19% are cited in the literature whereby the figures are distinctly higher for female patients in the first decade of life [ 25 ]. It would seem essential to give each case careful consideration taking into account the patient’s previous history and assessing the patient’s desire to have surgery.…”
Section: Discussionmentioning
confidence: 99%